Unique challenges in the Turkish workforce: examining the impact of job demands and resources on work-related outcomes of blue- and white-collar workers - İlhan, Ümit Deniz and Güler, Burcu Kümbül and Turgut, Dilara and Duran, Cem (Frontiers in Psychology, 2025)
IntroductionAn increasing body of research has explored the impact of job demands and resources on employee wellbeing and performance; however, empirical evidence remains limited regarding how these factors operate in non-Western contexts. Addressing this gap, the present study examines blue-collar (70.7%) and white-collar (29.3%) workers in Türkiye, investigating the effects of job demands (quantitative, cognitive, emotional) and job resources (leader support, co-worker support, trust) on emotional exhaustion, job satisfaction, organizational commitment, and intention to leave.MethodA total of 563 employees from three large production companies in Türkiye voluntarily participated in this study. Data were collected using the Turkish version of the Copenhagen Psychosocial Questionnaire (COPSOQ-III) for all constructs, except for intention to leave, which was assessed using the Michigan Organizational Assessment Questionnaire (MOAQ). The proposed relationships were analyzed through multi-group structural equation modeling (MG-SEM).ResultsJob demands significantly increased emotional exhaustion in both blue- and white-collar workers. However, while emotional exhaustion did not diminish organizational commitment among blue-collar workers, job satisfaction emerged as a key determinant in reducing their turnover intentions. In contrast, for white-collar workers, emotional exhaustion weakened organizational commitment, ultimately leading to higher turnover intentions. Moreover, job resources enhanced job satisfaction and indirectly reduced turnover intentions for blue-collar workers, whereas these resources did not significantly predict job satisfaction among white-collar workers.ConclusionThese findings underscore the importance of tailoring workplace strategies to different occupational groups in a non-Western setting. Strengthening job resources—particularly trust, leader support, and co-worker support—can enhance job satisfaction and reduce turnover risk among blue-collar workers. Conversely, for white-collar workers, mitigating job demands and managing emotional exhaustion are crucial for sustaining organizational commitment. This study contributes to the cross-cultural understanding of job demands and resources, highlighting their differential impact on blue- and white-collar workers in Türkiye.